JASALMA INTELLEKTTEN PAYDALANÍWDA JÚZEGE KELETUǴÍN AYÍRÍM MAShQALALAR - Prenov, B.B.; Atabaeva, B.J. (SCIENCE and SOCIETY, 2025)
The article discusses the experience of using artificial intelligence in the world's leading universities and the problems of artificial intelligence being applied in Uzbekistan.